Micromobility policies for sustainable transport: Bogotá and Mexico City - Karina Licea Vi\~nas (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2021)
This paper analyses regulations that support non-motorised mobility in Bogotá and Mexico City. It reviews the promotion of bicycles as a sustainable alternative to cars and the rapid implementation of cycling lanes as a substitute for public transport under the Covid-19 crisis. It also discusses the renewed interest in support for dockless micromobility sharing systems. It focuses on subsidies and revision of regulations as avenues to ensure that micromobility will make a durable contribution to sustainable mobility in these cities.
Keywords: 330; Stadtverkehr; Kommunale Verkehrspolitik; Nachhaltige Mobilität; Mexiko-Stadt; Bogota; Mexiko; Kolumbien